Similarities and seasonal variations in bacterial communities from the blood of rodents and from their flea vectors - Cohen, Carmit; Toh, Evelyn; Munro, Daniel; Dong, Qunfeng; Hawlena, Hadas (The ISME Journal, 2015)
Vector-borne microbes are subject to the ecological constraints of two distinct microenvironments: that in the arthropod vector and that in the blood of its vertebrate host. Because the structure of bacterial communities in these two microenvironments may substantially affect the abundance of vector-borne microbes, it is important to understand the relationship between bacterial communities in both microenvironments and the determinants that shape them. We used pyrosequencing analyses to compare the structure of bacterial communities in Synosternus cleopatrae fleas and in the blood of their Gerbillus andersoni hosts. We also monitored the interindividual and seasonal variability in these bacterial communities by sampling the same individual wild rodents during the spring and again during the summer. We show that the bacterial communities in each sample type (blood, female flea or male flea) had a similar phylotype composition among host individuals, but exhibited seasonal variability that was not directly associated with host characteristics. The structure of bacterial communities in male fleas and in the blood of their rodent hosts was remarkably similar and was dominated by flea-borne Bartonella and Mycoplasma phylotypes. A lower abundance of flea-borne bacteria and the presence of Wolbachia phylotypes distinguished bacterial communities in female fleas from those in male fleas and in rodent blood. These results suggest that the overall abundance of a certain vector-borne microbe is more likely to be determined by the abundance of endosymbiotic bacteria in the vector, abundance of other vector-borne microbes co-occurring in the vector and in the host blood and by seasonal changes, than by host characteristics.